Implikasi hukum penahanan validasi BPHTB terhadap developer sebagai wajib pajak mineral - Alvira Aslam; Abrar Saleng; Muh Hasrul (University of Merdeka Malang, 2022)
The results show that the Regional Government Polewali Mandar Regency has added housing developers to the taxpayers of NMMR to increase revenue from the lack of local revenue (LR) due to the income in the tax sector. Based on the research, the changing policies occurred because the Regent Regulation No. 13/2010 concerning NMMR Taxes did not explicitly stipulate who the taxpayers were to be subject to in the regulation, In addition, the lack of LR from the NMMR tax sector was caused by the rise of mining companies operating without Mining Business Permits (MBP). However, instead of controlling miners to increase revenue in the tax sector, the Government has instead designated housing developers as taxpayers of NMMR. In tax law, this policy breaches the principle of certainty which emphasizes the need for certainty regarding tax subjects and objects. In mining law, adding developers as taxpayers will only make unlicensed mining more prevalent. Meanwhile, in terms of housing and settlement law, this policy is detrimental to developers. Moreover, the existence of the delay of BPHTB if the developer refuses to become a taxpayer on NMMR taxes resulted in the developer being unable to process the contract and transfer the title.How to cite item: Aslam, A., Saleng, A., Hasrul, M. (2022). Implikasi hukum penahanan validasi BPHTB terhadap developer sebagai wajib pajak mineral. Jurnal Cakrawala Hukum, 13(1), 1-9. DOI:https://doi.org/10.26905/idjch.v13i1.7437.